Tinjauan Pelaksanaan Penyusutan Rekam Medis Inaktif di Rumah Sakit Islam Jakarta Cempaka Putih Tahun 2021 - Kurnia, Hanum Milla; Indawati, Laela; Rumana, Nanda Aula; Siswati, Siswati (Publikasi Indonesia, 2022)
Depreciation is an activity to reduce medical records from storage shelves by moving active medical records to inactive medical records. Depreciation of medical records needs to be done and considered, if the depreciation is not carried out with the addition of medical records that continues to increase, it will cause a buildup of medical record archives. This study aims to determine how the implementation of inactive medical record shrinkage at the Islamic Hospital Jakarta Cempaka Putih. This research method uses a descriptive method with a qualitative approach consisting of 3 informants, namely 1 head of medical records and 2 medical record officers. Based on the results of the study, it was found that the Islamic Hospital of Jakarta Cempaka Putih already had standard operating procedures related to shrinkage (retention) and destruction. The medical record unit depreciates medical records referring to the existing SOP. In carrying out the depreciation of the Jakarta Cempaka Putih Islamic Hospital, there were several things that had not been implemented, such as media transfer and extermination. The obstacle factors that occur in the implementation of depreciation are lack of human resources and there are still many medical records that accumulate because they have not been done entirely. Suggestions for the Islamic Hospital of Jakarta Cempaka Putih to make Standard Operating Procedures regarding the depreciation of inactive medical records, make decisions on medical records based on useful and not useful values, suggestions for Human Resources (HR) in the depreciation implementation section set a schedule so that the depreciation process can conducted.